A Theoretical Framework to Quantify Ecosystem Pressure‐Volume Relationships - Oliver Binks; Patrick Meir; Alexandra G. Konings; Lucas Cernusak; Bradley O. Christoffersen; William R. L. Anderegg; Jeffrey Wood; Lawren Sack; Jordi Martinez‐Vilalta; Maurizio Mencuccini (Global Change Biology, 2024)
‘Water potential’ is the biophysically relevant measure of water status in vegetation relating to stomatal, canopy and hydraulic conductance, as well as mortality thresholds; yet, this cannot be directly related to measured and modelled fluxes of water at plot‐ to landscape‐scale without understanding its relationship with ‘water content’. The capacity for detecting vegetation water content via microwave remote sensing further increases the need to understand the link between water content and ecosystem function. In this review, we explore how the fundamental measures of water status, water potential and water content are linked at ecosystem‐scale drawing on the existing theory of pressure‐volume (PV) relationships. We define and evaluate the concept and limitations of applying PV relationships to ecosystems where the quantity of water can vary on short timescales with respect to plant water status, and over longer timescales and over larger areas due to structural changes in vegetation. As a proof of concept, plot‐scale aboveground vegetation PV curves were generated from equilibrium (e.g., predawn) water potentials and water content of the above ground biomass of nine plots, including tropical rainforest, savanna, temperate forest, and a long‐term Amazonian rainforest drought experiment. Initial findings suggest that the stored water and ecosystem capacitance scale linearly with biomass across diverse systems, while the relative values of ecosystem hydraulic capacitance and physiologically accessible water storage do not vary systematically with biomass. The bottom‐up scaling approach to ecosystem water relations identified the need to characterise the distribution of water potentials within a community and also revealed the relevance of community‐level plant tissue fractions to ecosystem water relations. We believe that this theory will be instrumental in linking our detailed understanding of biophysical processes at tissue‐scale to the scale at which land surface models operate and at which tower‐based, airborne and satellite remote sensing can provide information.